Sabor e som: Sri Aurobindo, tradutor indiano (a busca de um centro em Auroville e Savitri) - Carlos Alberto Gohn (1994)
This researcher, as a member of a post-colonial society, recognizes himself in the experience of being de-centered. He shows, however, that Sri Aurobindo, creating himself as an Easterner, makes it possible for us to have an alternative experience of being de-centered. It is shown how, from the Hindu Vedic Experience translated, in a Peircean perspective, as an epic poem, Savitri, and as an Indian city, Auroville, the writings of Sri Aurobindo lead us to propose a mythical re-territorialization. The first four chapters of this dissertation answer the following questions: who translates? what gets translated? to whom? under which theoretical perspective? Chapters five and six show Sri Aurobindo as the one who can give us an archetypical experience of the axis mundi, in which a new man, supramentalised, builds himself poetically, appropriating the English language to de-colonize, in the first instance, his own Indian culture. Furthermore, Sri Aurobindo wants this experience to become widespread and ultimately universal. Following from that, the possibility presents itself, to the man so translated, to inhabit a new space, Auroville. The frame of reference of the research presented leads to the omparison between literature and cooking as well as Indian music and 1iterature.